Armazenamento de sementes de espécies nativas da Caatinga: caracterização morfoanatômica e germinação - Gonçalves, José Alexon Gomes (2015)
he exploitaition of Caatinga by extractive practices, as well as the formation of production systems based on monoculture, hurt the principles of sustainability and endangers the available resources, whether characterized by plants with wood or forage potential. Seed storage is a practice that contributes to the preservation of the genetic material in the fields and assists producers in the formation of pastures for animal feed. Species like Libidibia ferrea (Mart. Ex Tul.) L. P. Queiroz, the Merremia aegyptia (L.) Urban and Bauhinia cheilantha (Bong.) Steud., are examples of native plants from Caatinga, which have forage potential, are widely consumed by animals and, therefore, deserve attention with respect to the proper storage conditions of their seeds, aiming the use in the composition of pastures. The morphological and anatomical study of seeds also demonstrates considerable importance, so that, from this knowledge you can get information on germination, storage, viability and sowing methods, and enables practical applications in ecological studies in the management and conservation of flora and terrestrial fauna. Thus, this study aimed to evaluate the germination behavior, for nine months, of the three aforementioned species, packed in waterproof container (PET bottle), and stored in a cold chamber and laboratory environment, also to describe the seed morphological and anatomical reporting possible differences in the development of these with regard to storage environments. The seeds coats of L. ferrea and M. aegyptia presented pattern of similar structures, with exotesta consists of a rigid palisade layer, lucid line and mucilaginous layer, mesotesta formed by single layer of osteoesclereídes and endotesta formed by layers of parenchyma and sclerenchyma cells. In L. ferrea were observed glandular trichomes from the epidermal cells of the embryo toward the eophyll leaf primordia. B. cheilantha seed is albuminous, with foliaceous cotyledons, the coat is formed by two cells stratum and presents V-shaped hilo in the apical region. The different storage environments not provided morphoanatomical differences for L. ferrea and B. cheilantha seeds, but in M. aegyptia seeds, the cold chamber storage stimulated greater vascularization in the cotyledon. The seeds of L. ferrea showed better germination percentage when stored in a cold chamber (64, 64 and 48% at three, six and nine months, respectively). The seeds of M. aegyptia, stored in a cold chamber, showed fluctuation in germination (97, 86 and 99% at three, six and nine months, respectively). The germination of B. cheilantha decreased during the experimental period (93, 77 and 22% at 3, 6 and 9 months, respectively). In all species the germination speed index (GSI), showed better results at three months of storage